Cancer Connectors: Connexins, Gap Junctions, and Communication - Sinyuk, Maksim; Mulkearns-Hubert, Erin E.; Reizes, Ofer; Lathia, Justin (Frontiers in Oncology, 2018)
Despite concerted clinical and research efforts, cancer is a leading cause of death worldwide. Surgery, radiation, and chemotherapy have remained the most common standard-of-care strategies against cancer for decades. However, the side effects of these therapies demonstrate the need to investigate adjuvant novel treatment modalities that minimize the harm to healthy cells and tissues. Normal and cancerous cells require communication amongst themselves and with their surroundings to proliferate and drive tumor growth. It is vital to understand how intercellular and external communication impacts tumor cell malignancy. To survive and grow, tumor cells and their normal counterparts utilize cell junction molecules including gap junctions (GJs), tight junctions, and adherens junctions to provide contact points between neighboring cells and the extracellular matrix. GJs are specialized structures composed of a family of connexin proteins that allow for the free diffusion of small molecules and ions directly from the cytoplasm of adjacent cells without encountering the extracellular milieu, enabling rapid and coordinated cellular responses to internal and external stimuli. Importantly, connexins perform three main cellular functions. They enable direct gap junction intercellular communication (GJIC) between cells, form hemichannels to allow cell communication with the extracellular environment, and serve as a site for protein-protein interactions to regulate signaling pathways. Connexins themselves have been found to promote tumor cell growth and invasiveness, contributing to overall tumorigenicity and have arisen as attractive anti-tumor targets due to their functional diversity. However, connexins can also serve as tumor suppressors, and therefore, a complete understanding of the roles of connexins and GJs in physiological and pathophysiological conditions is needed before the application of connexin targeting strategies. Here, we discuss how the three aspects of connexin function, namely GJIC, hemichannel formation, and connexin-protein interactions, function in normal cells and contribute to tumor cell growth, proliferation, and death. Finally, we discuss the current state of anti-connexin therapies and speculate which role may be most amenable for the development of targeting strategies.